Children's school readiness in socioeconomically diverse pre-K classrooms. Issue 15 (17th November 2020) - Slicker, Gerilyn; Hustedt, Jason T.
ABSTRACT: Persisting socioeconomic gaps in school readiness have inspired research examining aspects of the pre-K experience that could reduce these gaps. A strategy that deserves consideration is the socioeconomic diversity of classrooms. In this literature review, we use ecological theory as a framework to present outcomes of socioeconomic diversity in U.S. pre-K settings on children's cognitive, language, and social-emotional skills, with language benefits being the most pronounced. We also evaluate parent, teacher, and peer contributions to children's school readiness in socioeconomically diverse pre-K settings. Research shows that children from all income backgrounds benefit in socioeconomically diverse learning environments – in academic preparedness and in other ways that prepare them for success in a diverse workforce and society. Evidence suggests that children from low-income families benefit most, which may reduce income-based gaps in school readiness. We conclude with recommendations for further research and discuss policy implications of increased socioeconomic diversity within pre-K programs.